At the king's command - Wiggs, Susan; Wiggs, Susan (Don Mills, Ont. : MIRA, 2009)
"Frustrated by his own failures at matrimony, King Henry VIII punishes an insolent nobleman by commanding him to marry the vagabond woman caught stealing his horse. Stephen de Lacey is a cold and bitter widower, long accustomed to the sovereign's capricious and malicious whims. He regards his new bride as utterly inconvenient ... though undeniably fetching. But Juliana Romanov is no ordinary thief--she is a Russian princess forced into hiding by the traitorous cabal who slaughtered her family. One day she hopes to return to Muscovy to seek vengeance. What begins as a mockery of a marriage ultimately blossoms into deepest love."--P. [4] of cover.
"Updated from the original publication Circle in the water, published by HarperCollins 1994"--T.p. verso.
Keywords: Princesses -- Russia; Forced marriage; Man-woman relationships; Great Britain -- History -- Henry VIII, 1509-1547; Love stories; Historical fiction